1992
DOI: 10.1111/j.1432-1033.1992.tb16559.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of carrot cDNA clones encoding a second putative proliferating cell‐nuclear antigen, DNA polymerase δ auxiliary protein

Abstract: The proliferating cell-nuclear antigen (PCNA) plays a key role in the control of eukaryotic DNA replication. We have isolated two cross-hybridizing groups of cDNA encoding carrot homologs of PCNA. Sequence analysis and Southern-blot experiments showed that the cDNA were derived from two distinct genes. One corresponded to the typical PCNA, which is known to be highly conserved in eukaryotes from yeast to man; its mRNA is 1.2 kb in size and the calculated molecular mass of the protein is 29 kDa. The other encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…An analogous phenomenon has been reported in carrot, where two PCNA genes, a short and a long one, were found. SpeciWcally, the long atypical carrot PCNA contains the short typical PCNA sequence with an extra C-terminal extension of unknown function (Hata et al 1992). Although the justiWcation of the existence of two related versions of PCNA transcripts is unclear, expression studies, performed in carrot somatic embryos, suggested that the long PCNA protein might act as a 'helper' of the short typical protein (Hata et al 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analogous phenomenon has been reported in carrot, where two PCNA genes, a short and a long one, were found. SpeciWcally, the long atypical carrot PCNA contains the short typical PCNA sequence with an extra C-terminal extension of unknown function (Hata et al 1992). Although the justiWcation of the existence of two related versions of PCNA transcripts is unclear, expression studies, performed in carrot somatic embryos, suggested that the long PCNA protein might act as a 'helper' of the short typical protein (Hata et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…SpeciWcally, the long atypical carrot PCNA contains the short typical PCNA sequence with an extra C-terminal extension of unknown function (Hata et al 1992). Although the justiWcation of the existence of two related versions of PCNA transcripts is unclear, expression studies, performed in carrot somatic embryos, suggested that the long PCNA protein might act as a 'helper' of the short typical protein (Hata et al 1992). It is also worth noting, that in various plants species, two PCNA genes encoding distinct PCNA family members were isolated (Lopez et al 1997;Touneille et al 2002;Strzalka et al 2009Strzalka et al , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…PCNA, however, may also exist as a dimeric ring. During somatic embryogenesis of Daucus carota, the carrot, two distinct PCNA genes are expressed (Hata et al, 1992). One encodes a typical size PCNA (264 amino acids) while the other encodes a longer form (365 amino acids).…”
Section: The Three Dimensional Structurementioning
confidence: 99%
“…PCNA has usually a size of 29 kDa, and it forms a trimeric hexagonal ring-shaped structure very similar to that of the ␤ subunit (37). Interestingly, it was recently reported that two PCNA genes were found in carrot, encoding putative PCNA molecules of 29 and 40 kDa (38). Based on its size, its trimeric structure and its activity as a processivity factor, ␤* could thus be viewed as an analog of the T4 gp45 and the eukaryotic PCNAs, with a possible evolutionary link.…”
Section: Discussionmentioning
confidence: 99%